Pengelolaan Limbah Domestik Rumah Tangga Menjadi Biokomposter Mikroorganisme Dengan Metode Aerob-Anaerob - Yessi Meridian Dini; Anis Aziza Zumroturida; Siti Sela Nurhalisa; Bagus Handi Saputra (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2020)
Biocomposter is one form of household waste management by processing waste into compost. Composting is the process by which organic material decomposes biologically, especially by microbes that utilize organic material as an energy source. The composting process runs aerobically and anaerobically in certain environmental conditions called the decomposition process. The purpose of this study was to determine the processing of solid domestic waste using the Bio Composter method and determine the effectiveness of the use of the remaining kitchen activities in domestic (household) waste treatment. In this study, using two programs, aerobic and anaerobic. The composition of the anaerobic biocomposter (with air) uses a perforated cover which is a mixture of composter from ready-made fertilizer (placed at the bottom), then then the banana skin that has been cut into small pieces first, after the banana peel is added to clay and finally put fertilizer ready-made composter. As for the composition of the aerobic biocomposter (without air), using a closed cover is first included composter fertilizer that is ready, then enter the banana skin that has been sliced into small pieces and placed neatly on the compost, then put the clay placed on top banana peels and finally put banana peels back on the clay. The results obtained are that the compost changes color to old brown, the temperature and pH are stable and the pungent aroma of waste has begun to diminish due to the appropriate composting process.